Aluminum Steam Oxidation in the Framework of Long‐Term Energy Storage: Experimental Analysis of the Reaction Parameters Effect on Metal Conversion Rate. Issue 9 (22nd July 2022) - Barelli, Linda; Trombetti, Lorenzo; Di Michele, Alessandro; Gammaitoni, Luca; Asenbauer, Jakob; Passerini, Stefano
Abstract : Aluminum is a promising material as an alternative green energy carrier thanks to its very high volumetric energy density and full recyclability. Aluminum oxidation with steam in the temperature range of 600–900 °C is investigated as an innovative and promising methodology for aluminum conversion resulting in hydrogen and heat production. Reaction times, hydrogen production rate and yield are assessed varying operational parameters such as temperature, steam to aluminum ratio, and gas hourly space velocity within the reactor. The conversion yield of aluminum is assessed at 73.13% at 900 °C and ambient pressure, with reaction times comparable with the one reported in the literature for water oxidation in batch‐pressurized reactors. Moreover, over 750 °C, alumina is produced in microparticles, allowing reactor operating times up to 1 h without incurring in the clogging effect. The obtained results are promising for the continuous operating condition of a future full‐scale reactor. Abstract : Aluminum is a promising green energy carrier thanks to its very high volumetric energy density (>23 kWh L −1 ) and full recyclability. Its conversion reaction with steam at high temperature (600–900 °C) results in hydrogen and heat production. The conversion yield of aluminum is assessed at 73.13% after 1 h at 900 °C and ambient pressure.